Postpartum Mom Mood Disorders - Faizah Betty Rahayuningsih (Jurnal EduHealth, 2023)
Postpartum mood disorder is a postpartum maternal psychological problem that includes a range of psychiatric disorders. Postpartum mood disorders can have a serious impact on both the mother and the baby. About 70-80% of women experience mood swings during pregnancy and postpartum. Some experience mild and temporary changes, while others experience significant depression or anxiety. Provides a brief overview of the issue of mood disorders, given their high impact globally. This review will cover aspects such as the prevalence of mood disorders, clinical manifestations, and relevant management strategies. Postpartum mood disorders have a high prevalence, both globally and in our country context. Risk factors include a history of psychiatric disorders, stress during pregnancy, lack of social support, and economic problems. Symptoms vary from mood swings, anxiety, sleep disturbances, to severe symptoms such as psychosis. These disorders can be life-threatening to both mother and baby if not detected and treated quickly. Early detection is crucial and using diagnostic tools such as the Edinburgh Postpartum Depression Scale can help. Treatment involves cognitive behavioral therapy, interpersonal therapy, and the use of medications such as antidepressants. This review is not only useful for increasing healthcare professionals' awareness of mood disorders in this period, but also provides important insights into providing appropriate and time-effective treatment. In the context of clinical significance, in addition to pharmacological treatment, interpersonal or cognitive-behavioral therapy, as well as family therapy, have a very important role in managing mood disorders during pregnancy and the postpartum period.